CALL and Complexity – Short Papers From EUROCALL 2019 2019
DOI: 10.14705/rpnet.2019.38.1042
|View full text |Cite
|
Sign up to set email alerts
|

Computer-mediated communication in Chinese as a second language learning: needs analysis of adolescent learners of Chinese at beginner level in Ireland

Abstract: Ireland’s new strategy for foreign language education, Languages Connect, identifies the establishment of Mandarin Chinese as a curricular language as a key goal for the coming years. Within the curriculum specification for Mandarin at Junior Cycle (ages 12-15), “using digital technology is identified as a core component: the student uses technology and digital media to learn, communicate, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…The issue of low averages for ISS categories implies that other factors such as a short telecollaboration period and potential technological problems cannot be neglected. The disconnection between the needs analysis (Wang et al, 2019) and findings in this study demonstrates that learners probably underestimated the challenge of engaging with native speakers, which would suggest that more scaffoldings and preparations are required for beginning-level learners before and during telecollaborations. More in-depth analysis to compare the pre and post changes of intercultural sensitivity among this group and the differences between Irish and Chinese participants will be discussed in an upcoming study.…”
Section: Discussioncontrasting
confidence: 66%
“…The issue of low averages for ISS categories implies that other factors such as a short telecollaboration period and potential technological problems cannot be neglected. The disconnection between the needs analysis (Wang et al, 2019) and findings in this study demonstrates that learners probably underestimated the challenge of engaging with native speakers, which would suggest that more scaffoldings and preparations are required for beginning-level learners before and during telecollaborations. More in-depth analysis to compare the pre and post changes of intercultural sensitivity among this group and the differences between Irish and Chinese participants will be discussed in an upcoming study.…”
Section: Discussioncontrasting
confidence: 66%
“…The study helps teachers to change their conventional mindset and opens up another alternative in helping students to learn better and easier. In supporting Ireland's latest strategy for Mandarin language education, Wang et al (2019) looked into the needs of initial Mandarin learners and their teacher. Even though the communication opportunities for Mandarin are lacking in Ireland, the study identified opportunities for meaningful communication and cultural learning that are helpful for students when they employ digital technology to learn the language.…”
Section: Introductionmentioning
confidence: 99%